The Christian Commonwealth : the organ of the progressive movement in religion and ethics. (London : Christian Commonwealth Company, 1910)
Specimen met op de voorpagina portretten van de volksvertegenwoordigers van de Labour Party in 1910
Bibliotheek Camille Huysmans
Engels
Krant
Keywords: Labour Party